Transition to distance learning during the COVID-19 pandemic: Efforts within the Higher Education sector in the United Arab Emirates (Journal of Applied Learning and Teaching, 2020)
In the UAE, the Ministry of Education (MOE) ordered the closure of higher education institutions’ facilities in March 2020 as a precautionary measure to contain COVID-19 and allowed online distance learning to take place. In this paper, a study on the readiness of higher education institutions in the UAE to transition to distance learning during the COVID-19 pandemic is conducted, and the preparedness of several institutions is discussed. In addition, this study highlights the foundations of the distance learning system adopted by higher education institutions along with the adopted educational platforms. MOE played a crucial role in this crisis by governing, monitoring and supporting the transition among universities to assure business continuity in higher education institutions. Moreover, higher education institutions encountered several challenges while implementing a distance learning system which is presented in this paper along with possible solutions and scenarios. Furthermore, multiple initiatives were launched by the UAE government to support distance learning that resulted in maintaining learning continuity among higher education students and faculty.